Application of the Sophisticated Thinking Blended Laboratory (STB-LAB) for Increasing Understanding in Using GIS for Physics Education Undergraduate Students in IPBA Lecture - Dirgantara, Yudi; Agustina, Rena Denya; Putra, Riki Purnama; Indrawan, Ivana Sylvi (Jurnal Pendidikan IPA Indonesia, 2024)
GIS is an application for conducting partial environmental analysis using data such as satellite imagery or surveys. In using GIS, of course, there are challenges in understanding the available features, which are very complex to understand. There are various difficulties in understanding the use of GIS applications, so a series of activities is needed to understand the use of GIS applications. This study aims to find out whether the STB-LAB can increase understanding of the use of GIS in undergraduate students, especially in the physics education department at the IPBA Lecture. The research method used in this study is a quasi-experimental quantitative method, with a two-group pretest-posttest design. The subjects used were 93 samples, with a purposive sampling technique. Paired sample t-test was conducted to test the hypothesis, followed by Cohen's D Effect Size test to provide details on the increase or decrease in the average gain. The results obtained in this study indicate that the STB-LAB-based laboratory activity model is able to increase understanding of the use of GIS applications for undergraduate physics education students by showing the hypothesis test obtained, namely Sig. 0.000, with an effect size of 1.022. In addition, there are additional findings, namely that female tend to prefer memorizing to understanding, compared to male who tend to prefer complex concepts to understanding.